2012
DOI: 10.1104/pp.111.188367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tomato Gene Functions Based on Coexpression Modules Using Graph Clustering and Differential Coexpression Approaches      

Abstract: Gene-to-gene coexpression analysis provides fundamental information and is a promising approach for predicting unknown gene functions in plants. We investigated various associations in the gene expression of tomato (Solanum lycopersicum) to predict unknown gene functions in an unbiased manner. We obtained more than 300 microarrays from publicly available databases and our own hybridizations, and here, we present tomato coexpression networks and coexpression modules. The topological characteristics of the netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 68 publications
0
64
0
Order By: Relevance
“…An increasing number of studies, based on the concept of the guilt by association (Quackenbush 2003), have shown the versatility of co-expression analysis. Gene co-expression analysis has been applied to identify and characterize various biological interactions, and has helped to predict gene function and analyze complex physiological traits in many plants, such as Arabidopsis (Movahedi et al 2011), tomato (Ozaki et al 2010Fukushima et al 2012), maize and rice (Ficklin and Feltus 2011). In this study, the survey of the co-expressed genes in different tissues and developmental stages of tomato fruit provided an overview on the groups of pivotal genes associated with the AsA metabolism.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…An increasing number of studies, based on the concept of the guilt by association (Quackenbush 2003), have shown the versatility of co-expression analysis. Gene co-expression analysis has been applied to identify and characterize various biological interactions, and has helped to predict gene function and analyze complex physiological traits in many plants, such as Arabidopsis (Movahedi et al 2011), tomato (Ozaki et al 2010Fukushima et al 2012), maize and rice (Ficklin and Feltus 2011). In this study, the survey of the co-expressed genes in different tissues and developmental stages of tomato fruit provided an overview on the groups of pivotal genes associated with the AsA metabolism.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Expression profiling analysis has been widely used to predict potential biological functions of genes (Fukushima et al 2012;Li et al 2006). Here, we explored the transcriptome-tophenotype relations by comparing LecRK expression profiles retrieved from publicly available microarray data with the mutant phenotypes obtained in this study (Fig.…”
Section: Are There Associations Between Lecrk Mutant Phenotypes and Lmentioning
confidence: 99%
“…Genes that exhibit similar expression patterns are often expected to be involved in the same biological processes (Eisen et al 1998;Fukushima et al 2012). We computed coexpression profiles of all LecRK in leaves inoculated with P. infestans and DC3000 over time.…”
Section: Are There Associations Between Lecrk Mutant Phenotypes and Lmentioning
confidence: 99%
“…Only data sets that passed quality control test by their original authors were chosen. Normalized matrices were retrieved from Mintz-Oron et al (2008), Adato et al (2009), andFukushima et al (2012). These matrices included 32 profiles (after uniting replicates and dividing by the control) from fruit tissues (the fruit data set) and 21 profiles (after uniting replicates and dividing by control) of root and leaf tissues (the root and leaf data set).…”
Section: Tomato Datamentioning
confidence: 99%